Lima1 mediates the pluripotency control of membrane dynamics and cellular metabolism - Duethorn, Binyamin; Groll, Fabian; Rieger, Bettina; Drexler, Hannes C. A.; Brinkmann, Heike; Kremer, Ludmila; Stehling, Martin; Borowski, Marie-Theres; Mildner, Karina; Zeuschner, Dagmar; Zernicka-Goetz, Magdalena; Stemmler, Marc; et al. (Nature Communications, 2022)
Lima1 is an extensively studied prognostic marker of malignancy and is also considered to be a tumour suppressor, but its role in a developmental context of non-transformed cells is poorly understood. Here, we characterise the expression pattern and examined the function of Lima1 in mouse embryos and pluripotent stem cell lines. We identify that Lima1 expression is controlled by the naïve pluripotency circuit and is required for the suppression of membrane blebbing, as well as for proper mitochondrial energetics in embryonic stem cells. Moreover, forcing Lima1 expression enables primed mouse and human pluripotent stem cells to be incorporated into murine pre-implantation embryos. Thus, Lima1 is a key effector molecule that mediates the pluripotency control of membrane dynamics and cellular metabolism.
CRIS-Team Scopus Importer:2022-02-11